Famine and disease in Ireland.
1 online resource (338 pages)
Keywords: The Great Famine of 1845-9 remains the great climacteric in Irish history. This title contains reprints of contemporary works relating to the Great Famine, including writings on the medical conditions in Ireland at the time gathered from the "Dublin Journal of Medical Science" and similar publications.